A CARE-compliant article: a case report of possible association between recurrence of multiple evanescent white dot syndrome and the Herpesviridae family. Issue 15 (April 2020) - Haw, Yu-Lin; Yu, Teng-Chieh; Yang, Chang-Sue
Abstract: Rationale: Multiple evanescent white dot syndrome (MEWDS) is a self-limited multifocal chorioretinopathy that typically affects otherwise healthy young females in the second to fourth decades of life. Current understanding of the pathophysiology of MEWDS is still limited. One of the possible underlying causes is an infectious etiology. Patient concerns: A 24-year-old female with recurrent episodes of typical MEWDS ocular manifestation was observed over 2 years. Viral-specific antibody serologic tests showed evidence of exposure to the Herpesviridae family during the acute stage of MEWDS in the first and recurrent episodes. Diagnoses: MEWDS was diagnosed by the clinical findings and ancillary testing results of fundus photography, optical coherence tomography, fluorescein angiography, indocyanine green angiography and electroretinogram. The laboratory serology data was positive for varicella-zoster virus (VZV) immunoglobulin M (IgM) in the first episode and exhibited high Epstein–Barr virus (EBV) elevated immunoglobulin G (IgG) titer in the recurrent episode. Interventions: Due to the self-limited nature of MEWDS, we observed the clinical course without intervention. Outcomes: During acute onset of MEWDS, serologic data for VZV IgM antibody was positive in the first episode. Two years later, the patient had recurrent episodes of MEWDS in the contralateral eye. Serologic study showed highly elevated IgG titer (1:160) of Epstein-Barr virus capsid antigen (EB-VCA) in the acute stage. The follow-up paired serum virus serology test showed that the prior EB-VCA IgG titer decreased fourfold to 1:40 in the recovery stage. Lessons: Recurrence of MEWDS may be associated with acute systemic infection of the Herpesviridae family or virus-induced autoimmune inflammatory reaction.